2016
DOI: 10.1590/1982-0224-20150030
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of Ochmacanthus batrachostoma (Miranda-Ribeiro, 1912) (Siluriformes: Trichomycteridae): a possible case of incipient paedomorphism

Abstract: The lepidophagous stegophiline catfish Ochmacanthus batrachostoma (Miranda-Ribeiro, 1912) is endemic to the Paraná-Paraguai basin and is the only member of its genus in that drainage. It remains a poorly-known taxon mainly due to the historical scarcity of study specimens. The species is herein redescribed on the basis of type and non-type specimens from Brazil, Argentina and Paraguay. Ochmacanthus batrachostoma can be distinguished from congeners by the presence of long maxillary and rictal barbels, reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
3
0
4
Order By: Relevance
“…The vandeliines feed exclusively on blood from the gills of other fishes (Kelley and Atz, 1964;Machado and Sazima, 1983) while the stegophilines have been reported as scale and mucus-feeders (Eigenmann and Allen, 1942;Roberts, 1972;Baskin et al, 1980;Machado and Sazima, 1983;Winemiller and Yan, 1989;Neto and de Pinna, 2016). The feeding habits of the representatives of a third subfamily, the Tridentinae, remains uncertain, but there are circumstantial records of semiparasitic (scale-eating) or predation of small invertebrates among its species.…”
Section: Introductionmentioning
confidence: 99%
“…The vandeliines feed exclusively on blood from the gills of other fishes (Kelley and Atz, 1964;Machado and Sazima, 1983) while the stegophilines have been reported as scale and mucus-feeders (Eigenmann and Allen, 1942;Roberts, 1972;Baskin et al, 1980;Machado and Sazima, 1983;Winemiller and Yan, 1989;Neto and de Pinna, 2016). The feeding habits of the representatives of a third subfamily, the Tridentinae, remains uncertain, but there are circumstantial records of semiparasitic (scale-eating) or predation of small invertebrates among its species.…”
Section: Introductionmentioning
confidence: 99%
“…a). Ochmacanthus candirus are known for being mucophagous and are likely clinging to the botos with their sucker‐like apparatus and teeth (see Zuanon and Sazima , Neto and de Pinna ). Burst series of photographs and underwater video images showed that some candirus can move quite freely, quickly, and frequently around the body of the botos.…”
Section: Resultsmentioning
confidence: 99%
“…Distribuição Nacional Estados Mato Grosso, Mato Grosso do Sul Biomas Pantanal Bacias Hidrográficas Sub-bacia Paraguai 01, Sub-bacia Paraguai 02, Sub-bacia Paraguai 03 (Neto & de Pinna, 2016).…”
Section: Distribuição Globalunclassified
“…Endêmica do Brasil: Não Ochmacanthus batrachostoma é conhecida das bacias dos rios Paraguai e Paraná, na na Bolívia (Sarmiento et al, 2014), Brasil, Paraguai e na Argentina (Neto & de Pinna, 2016).…”
Section: Distribuiçãounclassified

Ficha de Ochmacanthus batrachostoma

Alberto Akama,
André Luiz Netto Ferreira,
Bruno Francelino de Melo
et al. 2024
Datasets - Sistema SALVE - ICMBio